# cos3a

We will learn how to express the multiple angle of cos 3A in terms of A or cos 3A in terms of cos A.

Trigonometric function of cos 3A in terms of cos A is also known as one of the double angle formula.

Bạn đang xem: cos3a

If A is a number or angle then we have, cos 3A = 4 cos^3 A - 3 cos A

Now we will proof the above multiple angle formula step-by-step.

Proof: cos 3A

= cos (2A + A)

= cos 2A cos A - sin 2A sin A

= (2 cos^2 A - 1) cos A - 2 sin A cos A ∙ sin A

= 2 cos^3 A - cos A - 2 cos A (1 - cos^2 A)

= 2 cos^3 A - cos A - 2 cos A + 2 cos^3 A

= 4 cos^3 A - 3 cos A

Therefore,  cos 3A = 4 cos^3 A - 3 cos A             Proved

Note:  (i) In the above formula we should note that the angle on the R.H.S. of the formula is one-third of the angle on L.H.S. Therefore, cos 120° = 4 cos^3 40° - 3 cos 40°.

(ii) To find the formula of cos 3A in terms of A or cos 3A in terms of cos A we have use cos 2A = 2cos^2 A - 1.

Now, we will apply the formula of multiple angle of cos 3A in terms of A or cos 3A in terms of cos A vĩ đại solve the below problems.

1. Prove that: cos 6A = 32 cos^6 A - 48 cos^4 A + 18 cos^2 A - 1

Solution:

L.H.S. = cos 6A

= 2 cos^2 3A - 1, [Since we know that, cos 2θ = 2 cos^2 θ - 1]

= 2(4 cos^3 A - 3 cos A)^2 - 1

= 2 (16 cos^ 6 A + 9 cos^2 A - 24 cos^2 A) - 1

= 32 cos^6 A – 48 cos^4 A + 18 cos^2 A - 1 = R.H.S.

2. Show that, 32 sin^6 θ = 10 - 15 cos 2θ + 6 cos 4θ - cos 6θ

Solution:

Xem thêm: coi phim lý tiểu long

L.H.S = 32 sin^6 θ

= 4 ∙ (2 sin^2 θ)^3

= 4 (1 - cos 2θ)^3

= 4 [1 - 3 cos 2θ + 3 ∙ cos^2 2θ - cos^3 2θ]

= 4 - 12 cos^2 θ + 12 cos^2 2θ - 4 cos^3 2θ

= 4 - 12 cos 2θ + 6 ∙ 2 cos^2 2θ   - [cos 3 ∙ (2θ) + 3 cos 2θ]

[Since, cos 3A = 4 cos^3 A - 3 cos A

Therefore, 4 cos^3 A = cos 3A + 3 cos A]

⇒ 4 cos^3 2θ = cos 3 ∙ (2θ) + 3 cos 2θ, (replacing A by 2θ)

= 4 - 12 cos 2θ + 6 (1 + cos 4θ) - cos 6θ - 3 cos 2θ

= 10 - 15 cos 2θ + 6 cos 4θ - cos 6θ = R.H.S.                 Proved

3. Prove that: cos A cos (60 - A) cos (60 + A) = ¼ cos 3A

Solution:

L.H.S. = cos A ∙ cos (60 - A) cos (60 + A)

= cos A ∙ (cos^2 60 - sin^2 A), [Since we know that cos (A + B) cos (A - B)          = cos ^2 A - sin ^2 B]

= cos A (¼ - sin^2 A)

= cos A (¼ - (1 - cos^2 A))

= cos A (-3/4 + cos ^2 A)

= ¼ cos A (-3 + 4 cos^2 A)

= ¼(4 cos^3A - 3 cos A)

Xem thêm: siêu nhân anh hùng

= ¼ cos 3A = R.H.S.                        Proved

Multiple Angles

• sin 2A in Terms of A
• cos 2A in Terms of A
• tan 2A in Terms of A
• sin 2A in Terms of tan A
• cos 2A in Terms of tan A
• Trigonometric Functions of A in Terms of cos 2A
• sin 3A in Terms of A
• cos 3A in Terms of A
• tan 3A in Terms of A
• Multiple Angle Formulae

Didn't find what you were looking for? Or want vĩ đại know more information about Math Only Math. Use this Google Search vĩ đại find what you need.